SA PANGAMBE SA PANAILI “SEBUAH KARYA TARI TERINSPIRASI DARI RITUAL MARPANGIR DI KABUPATEN MANDAILING NATAL” - Rasmida Rasmida; Sahrul N; Siti Pratiwi Agmaulida Fatrion (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2021)
People of Mandailing Natal have a tradition called Marpangir which was done by the ancestors in the ancient time. It is an activity of self-cleaning as a form of welcoming the holy month of Ramadhan. This tradition has several values such as cultural, ethical, religious and social values. Along with the world's development, this ritual has had changes in terms of the way it is done and the ingredients used. Concerns have been raised by researchers regarding the differences of values that appear among the young generations nowadays, which then leads to individualist personnels. These phenomena are interpreted and expressed through publications related. Looking back on the old days, young generations in Mandailing Natal had a strong sense of togetherness and created a saying